Bioactive peptides fractions from traditional Iranian Koopeh cheese; lactic fermentation products. (October 2020) - Banihashemi, Seyed Alireza; Nikoo, Mehdi; Ghasempour, Zahra; Ehsani, Ali
Abstract: Koopeh is a traditional Iranian cheese produced from raw milk of sheep or cow, famous for its specific taste and ripening process. In this study, the antimicrobial and antioxidant activities of water-soluble extracts (WSEs) from different Koopeh cheese samples (C1–C8) were evaluated. The WSEs had considerable antimicrobial activity against Pseudomonas aeruginosa, Bacillus cereus and Salmonella enterica . Free radical scavenging of ABTS and DPPH ranges were 56.5–89.9% and 48.7–77.8%, respectively, while iron chelating activities of up to 88.8% were demonstrated. Samples with maximum antioxidant activity (C3 and C5) were selected for further analysis. Different ultrafiltrated fractions (<2, 2–10, and >10 kDa) of C3 and C5 samples were tested, and the 2–10 kDa fraction of C3 showed the highest antioxidant activity. Based on MALDI-TOF/MS analysis, peptides with molecular weights of 3896.91, 3937.42, 3926.57, 3702.51 and 3692.87 Da were dominant in 2–10 kDa fraction. Our results indicated that Koopeh cheese is a potential functional food, and that its peptide fractions can be employed in nutraceutical formulations. Graphical abstract: Image 1 Highlights: Water-soluble extract from Koopeh cheeses had potent antioxidant and antimicrobial activities. The WSEs showed antimicrobial activity against P. aeruginosa, B. cereus and S. enterica. Peptides fraction of 2–10 kDa was possessed the highest antioxidant activity. MALDI-TOF-MS analysis revealed peptides with molecular weight ~4 kDa.